Variação e gramaticalização no uso de preposições em contextos de verbos de movimento no português brasileiro - Wiedemer, Marcos Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The objective of this thesis is to investigate the variation and change of prepositions, involving prepositions a/para/em introducing locative complement of motion verbs (caminhar (walk), chegar (arrive), entrar (come in), ir (go), levar (take), mudar (move), partir (leave), sair (go out), voltar (come back)) through grammaticalization. Therefore, this investigation is supported by framework of Grammaticalization (HOPPER, 1991, HOPPER; TRAUGOTT, 1993, LEHMANN, 2002) and Sociolinguistics (WEINREICH; LABOV; HERZOG, 1968, LABOV, 1972, 1978, 2001). Aiming to combine present and past in search of dynamic and fluid relations between form and function, we investigated samples of Brazilian Portuguese from two synchronies: speech sample of XXI century extracted from samples of spoken Portuguese in the northwestern area of São Paulo state (Linguistic Sample from São Paulo State Project: GONÇALVES, 2007, 2008a, 2008b), and writing sample of XIX century, constituted by written texts. The objective is to reconstitute clines of changing occurred in the contexts of motion verbs in Brazilian Portuguese. The results demonstrate that these prepositions designate exclusively space notions, and the location notions is provided by the semantic and syntactic valency of the verb. The differences of meaning which update the prepositions are derived from a regular relationship between basic meaning and generic meaning, and the gradual increase of pragmatization (inference) and abstractization (metaphoric strategies) of meaning in the use of these prepositions. In contemporary Portuguese, we found the process of stable variation of the prepositions 'em' and 'para' with greater meaning abstractization, which explains the inclusion of new types of complements and the influence of social and linguistic factors in the selection of a specific preposition, and a process of decline the gradual preposition 'a'. Furthermore, we showed that there is a process of ...

O objetivo desta tese é investigar a variação e a mudança, via gramaticalização, envolvendo as preposições a/para/em que introduzem complementos locativos de verbos de movimento (caminhar, chegar, entrar, ir, levar, mudar, partir, sair, voltar). Embasam, portanto, esta investigação postulados da Gramaticalização (HOPPER, 1991, HOPPER; TRAUGOTT, 1993, LEHMANN, 2002) e da Sociolinguística (WEINREICH; LABOV; HERZOG, 1968, LABOV, 1972, 1978, 2001). Procurando conjugar presente e passado na busca de relações dinâmicas e fluidas entre forma e função, investigamos amostras do português brasileiro provenientes de duas sincronias: amostra de fala do século XXI, proveniente do português falado na região noroeste do estado de São Paulo (Projeto Amostra Linguística do Interior Paulista: GONÇALVES, 2007, 2008a, 2008b), e amostra de escrita do século XIX, proveniente de textos escritos, com o objetivo de mapear os aclives de mudanças por que passam as preposições ligadas ao complemento locativo de verbos de movimento no português brasileiro. Os resultados demonstram que essas preposições designam exclusivamente relações espaciais, e a relação local, em vez disso, está implícita na valência semântica e sintática do verbo. As diferenças de significados nos usos das preposições decorrem de uma relação regular entre um significado básico e um significado genérico e do aumento gradual da pragmatização (inferência) e abstratização (estratégias metafóricas) no uso dessas preposições. No português contemporâneo, constatamos o processo de variação estável das preposições em e para com maior abstratização de significado, fato que explica a inserção de novos tipos de complementos e a atuação de fatores sociais e linguísticos na seleção de uma determinada preposição, e um processo de recuo gradativo da preposição a. Além disso, evidenciamos que há um processo de generalização por ...
Keywords: Linguística; Língua portuguesa - Gramaticalização; Língua portuguesa - Brasil; Língua portuguesa - Variação; Lingua portuguesa - Preposições; Portuguese language Grammaticalization